Methodological Consequences of Situation Specificity: Biases in Assessments - Patry, Jean-Luc (Frontiers in Psychology, 2011)
Social research is plagued by many biases. Most of them are due to situation specificity of social behavior and can be explained using a theory of situation specificity. The historical background of situation specificity in personality social psychology research is briefly sketched, then a theory of situation specificity is presented in detail, with as centerpiece the relationship between the behavior and its outcome which can be described as either “the more, the better” or “not too much and not too little”. This theory is applied to reliability and validity of assessments in social research. The distinction between “maximum performance” and “typical performance” is shown to correspond to the two behavior-outcome relations. For maximum performance, issues of reliability and validity are much easier to be solved, whereas typical performance is sensitive to biases, as predicted by the theory. Finally, it is suggested that biases in social research are not just systematic error, but represent relevant features to be explained just as other behavior, and that the respective theories should be integrated into a theory system.